Sleep and mood disorders in dry eye disease and allied irritating ocular diseases - Ayaki, Masahiko (Sci Rep, 2016)
The aim of the present study was to evaluate sleep and mood disorders in patients with irritating ocular diseases. The study design was a cross-sectional/case-control study conducted in six eye clinics. Out of 715 outpatients diagnosed with irritating ocular surface diseases and initially enrolled, 301 patients with dry eye disease (DED) and 202 age-matched control participants with other ocular surface diseases were analyzed. The mean Pittsburgh Sleep Quality Index (PSQI) and Hospital Anxiety and Depression Scale (HADS) scores were 6.4 ± 3.2 and 11.1 ± 5.7 for severe DED (n = 146), 5.5 ± 3.3 and 9.8 ± 4.0 for mild DED (n = 155), 5.5 ± 3.1 and 9.5 ± 6.6 for chronic conjunctivitis (n = 124), and 5.0 ± 3.3 and 8.9 ± 5.3 for allergic conjunctivitis (n = 78). There were significant differences among these diagnostic groups for PSQI (P < 0.05). Regression analysis of patients with DED revealed the PSQI and HADS scores were significantly correlated with the severity of DED (P < 0.05). Our results demonstrate that sleep quality in patients with DED is significantly worse than in patients with other irritating ocular surface diseases and it is correlated with the severity of DED.